2009
DOI: 10.1016/j.exger.2008.12.001
|View full text |Cite
|
Sign up to set email alerts
|

The deficit in long-term potentiation induced by chronic administration of amyloid-β is attenuated by treatment of rats with a novel phospholipid-based drug formulation, VP025

Abstract: , et al.. The deficit in long-term potentiation induced by chronic administration of amyloid-β-is attenuated by treatment of rats with a novel phospholipid-based drug formulation, VP025. Experimental Gerontology, Elsevier, 2009, 44 (4), pp.300. <10.1016/j.exger.2008.12.001>. Accepted ManuscriptThe deficit in long-term potentiation induced by chronic administration of amyloid-β-is attenuated by treatment of rats with a novel phospholipid-based drug formulation, VP025 This is a PDF file of an uned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Some of these studies have observed memory impairment following single brain infusion (Lesné et al, 2006;Shankar et al, 2008), but the toxicity of small A␤ 1-42 oligomers in vivo still needs to be established. The A␤ toxicity could not be determined using an osmotic pump system for prolonged administration of more mature A␤ species, which dynamically continues to oligomerize during this time and may stick into the pump (Malm et al, 2006;Miller et al, 2009;Ji et al, 2011). Other reports have shown that transgenic models overexpressing A␤ develop early synaptic alterations but lack the extensive cell death seen at the onset of memory decline in AD (Irizarry et al, 1997;Chishti et al, 2001;Oddo et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies have observed memory impairment following single brain infusion (Lesné et al, 2006;Shankar et al, 2008), but the toxicity of small A␤ 1-42 oligomers in vivo still needs to be established. The A␤ toxicity could not be determined using an osmotic pump system for prolonged administration of more mature A␤ species, which dynamically continues to oligomerize during this time and may stick into the pump (Malm et al, 2006;Miller et al, 2009;Ji et al, 2011). Other reports have shown that transgenic models overexpressing A␤ develop early synaptic alterations but lack the extensive cell death seen at the onset of memory decline in AD (Irizarry et al, 1997;Chishti et al, 2001;Oddo et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In another finding, PEG and anti-Aβ Abs-coated CNPs (Aβ-CNPs-PEG) protected against oxidative stress/Aβ-mediated neurodegeneration through the brain-derived neurotrophic factor (BDNF) signaling pathway [56]. Another study found that anti-inflammatory phosphatidylglycerol-based phospholipid NPs (VP025) attenuated Aβ-induced long-term potentiation deficits by inhibiting caspase-3 activation [57]. Recent efforts have focused on exploiting NPs as drug carriers into the brain.…”
Section: Targeting Other Ad Pathogenesismentioning
confidence: 98%
“…[202] Apart from the above NPs, the anti-inflammatory phosphatidylglycerol phospholipid nanoparticles (VP025) can also memorably inhibit the activation of caspase-3 in the hippocampus to improve the memory impairment of AD. [203] Lipid nanoparticles can be administered by intraperitoneal injection, which is very convenient. Such a relatively small size of nanoparticles meets with the absorption of drugs required so as not to jam the lungs and other organs, leading to animal deaths.…”
Section: Lipid Nanoparticles (Lnp)mentioning
confidence: 99%